2005
DOI: 10.1002/ejoc.200500240
|View full text |Cite
|
Sign up to set email alerts
|

Metalation and Derivatization of All Six Dichlorobenzotrifluorides:Site Selectivities

Abstract: The metalation of 2,3-, 2,6-, 2,4-and 3,5-dichlorobenzotrifluorides can be readily effected with standard reagents such as lithium diisopropylamide, lithium 2,2,6,6-tetramethylpiperidide, and butyllithium at the chlorine-adjacent 4-and 3-positions and the chlorine-flanked 3-and 4-positions, respectively. However, regioselectivity was secured with 2,6-dichlorobenzotrifluoride only under equilibrating conditions as the initial deprotonation occurs simultaneously at the 3-and 4-positions. 3,4-Dichlorobenzotrifluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…This result suggested that a regioselectivity suitable for our purpose, i.e., lithiation ortho to the 1,3-dioxolan-2-yl group, could be achieved only if the common ortho position to the two chloro substituents is blocked, e.g., by introducing the easily removable trimethylsilyl group. 12,13 Thus, the lithio derivative obtained by reaction of 4 with butyllithium at -78 °C in THF was treated with chloro(trimethyl)silane, affording compound 7 in high yield. As expected from our earlier studies (Figure 2), lithiation of the silylated derivative 7 with butyllithium in THF at -78 ° occurred exclusively in the chloro-substituted ring, as demonstrated by the formation of derivatives 8 and 9, respectively, after reaction with the corresponding electrophiles.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This result suggested that a regioselectivity suitable for our purpose, i.e., lithiation ortho to the 1,3-dioxolan-2-yl group, could be achieved only if the common ortho position to the two chloro substituents is blocked, e.g., by introducing the easily removable trimethylsilyl group. 12,13 Thus, the lithio derivative obtained by reaction of 4 with butyllithium at -78 °C in THF was treated with chloro(trimethyl)silane, affording compound 7 in high yield. As expected from our earlier studies (Figure 2), lithiation of the silylated derivative 7 with butyllithium in THF at -78 ° occurred exclusively in the chloro-substituted ring, as demonstrated by the formation of derivatives 8 and 9, respectively, after reaction with the corresponding electrophiles.…”
Section: Figurementioning
confidence: 99%
“…The compounds synthesized are useful intermediates for the synthesis of heterocyclic derivatives. The trimethylsilyl 13,17 and ethylene ketal 2,18,19 protecting groups can be removed at a convenient stage of the subsequent synthetic route under conventional conditions. Just as examples, compound 6 was prepared by desilylation of the derivative 10, and the ketal 9 was hydrolyzed to the benzophenone 11.…”
Section: Figurementioning
confidence: 99%
“…Site-specific metalation and trapping of the resulting intermediates with a variety of electrophiles open a comfortable entry to new building blocks for lifescience-oriented research and thus help combinatorial synthesis to escape from the prison of catalogue chemicals. [31] …”
Section: Introduction 5433mentioning
confidence: 97%
“…[30] For example, 2,6-dichlorobenzotrifluoride was prepared in this way, for the first time, by lithiation and subsequent iodination of 1,3-dichlorobenzene and subsequent treatment with (trifluoromethyl)trimethylsilane in the presence of cuprous iodide and spray-dried potassium fluoride (Scheme 1). [31] The subsequent reaction of this 2,6-dichlorobenzotrifluoride with lithium 2,2,6,6-tetramethylpiperidide (LITMP) and carbon dioxide afforded 2,4-dichloro-3-(trifluoromethyl)benzoic acid (1, 71 % yield). [31] Although the other five dichlorobenzotrifluorides are all commercial compounds, functionalized derivatives thereof were thus far unknown.…”
Section: Introduction 5433mentioning
confidence: 99%
See 1 more Smart Citation